Digital design and computer architecture - Harris, Sarah L.; Harris, David Money (Morgan Kaufmann, 2016)
Digital Design and Computer Architecture: ARM Edition takes a unique and modern approach to digital design. Beginning with digital logic gates and progressing to the design of combinational and sequential circuits, Harris and Harris use these fundamental building blocks as the basis for what follows: the design of an actual ARM processor. With over 75% of the world's population using products with ARM processors, the design of the ARM processor offers an exciting and timely application of digital design while also teaching the fundamentals of computer architecture. SystemVerilog and VHDL are integrated throughout the text in examples illustrating the methods and techniques for CAD-based circuit design. By the end of this book, readers will be able to build their own microprocessor and will have a top-to-bottom understanding of how it works. Harris and Harris have combined an engaging and humorous writing style with an updated and hands-on approach to digital design.